Importance of metastases in the internal mammary chain in the treatment of breast cancer - Cáceres G., Eduardo (2015)
The involvement of the Internal Mammary Chain has been investigated in an unselected consecutive serie of 94 cases of carcinoma of the breast. In 18 cases or 19.1 per cent metastasis were found in the internal mammary chain, in 2 of which the axillary lymph nodes had not been invaded. Invasion of the internal mammary chain was present in 27.6 per cent when there was metastasis to the axillary lymph nodes and the greater the degree of axillary involvement the more likely it is that the internal mammary chain will be invaded. The location of the tumor plays an important role in the incidence of internal mammary chain involvement. The internal mammary chain was invaded in 43.4 per cent when the tumor was situated in the inner half of the breast and 21.4 per cent when it was in the sub-aereolar region of the breast and 8.7 per cent when it was located in the outer half of the breast. The typical classical mastectomy as was described by Halsted-Meyer does not represent in sorne instanccs the rational treatment of cancer of the breast and perhaps explain the reason of fails in some cases of breast carcinoma.